2010
DOI: 10.1016/s0027-9684(15)30732-x
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Stigma in Young Adults With Sickle Cell Disease

Abstract: Health-related stigma is increasingly becoming a major public health issue that is receiving more attention. Young adults with sickle cell disease (SCD) are at risk for health-related stigmatization due to the many challenges of the disease. SCD includes the lifelong challenges of managing the chronic illness while accessing and navigating the health care system. The burdens of the disease can affect all aspects of the lives of individuals with SCD to include physiological, psychological, and social well-being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
111
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 61 publications
0
111
0
Order By: Relevance
“…However, based on prior research, sickle cell disease patients, who in the U.S. are nearly all African-American, might receive less analgesia than racial majority members, and might more often be suspected of malingering, of being dependent on opioids, or of being psychologically addicted than those with the "control" conditions. [26] We found that both estimated rates of opioid addiction (defined by the caregiver) and estimated rates of withdrawal symptoms were consistently higher for either sickle cell disease patients or chronic pancreatitis patients than for low back pain patients. However, these rates were not estimated statistically significantly higher for sickle cell disease patients than for chronic pancreatitis patients, though numeric estimates were higher for sickle cell disease patients.…”
Section: Discussionmentioning
confidence: 75%
“…However, based on prior research, sickle cell disease patients, who in the U.S. are nearly all African-American, might receive less analgesia than racial majority members, and might more often be suspected of malingering, of being dependent on opioids, or of being psychologically addicted than those with the "control" conditions. [26] We found that both estimated rates of opioid addiction (defined by the caregiver) and estimated rates of withdrawal symptoms were consistently higher for either sickle cell disease patients or chronic pancreatitis patients than for low back pain patients. However, these rates were not estimated statistically significantly higher for sickle cell disease patients than for chronic pancreatitis patients, though numeric estimates were higher for sickle cell disease patients.…”
Section: Discussionmentioning
confidence: 75%
“…Also the effect of HIV on people with genetic defect condition such as Sickle Cell Anaemia has been documented [4] [5]. However, studies of the prevalence and the effect of HIV on Sickle Cell Anemia subjects have not been well elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of stigmatisation and marginalisation on those with SCD is recognised as a feature of their lives in school, in the workplace, and in the healthcare setting (Anderson & Asnani, 2013;Forrester et al, 2015;Jenerette & Brewer, 2010;Jenerette, Funk, & Murdaugh, 2005). More broadly, the experience of stigmatisation is known to be associated with depression, anxiety, and suicidal ideation (Goffman, 1963;Jenerette & Brewer, 2010;Jenerette et al, 2005) and hence the probability that stigma increases the burden on patients with SCD and families (Jenerette & Brewer, 2010).…”
Section: (Participant 1 Mother)mentioning
confidence: 99%
“…More broadly, the experience of stigmatisation is known to be associated with depression, anxiety, and suicidal ideation (Goffman, 1963;Jenerette & Brewer, 2010;Jenerette et al, 2005) and hence the probability that stigma increases the burden on patients with SCD and families (Jenerette & Brewer, 2010). It is so and as Helman (2007) wrote that; "symptoms achieve their meaning in relation to physiological states which are interpreted as the referents of the symptoms" (p.122).…”
Section: (Participant 1 Mother)mentioning
confidence: 99%
See 1 more Smart Citation